An Optimization Method for Critical Node Identification in Aviation Network - Zhang, Haixia; Zhao, Jingjie; Wang, Jiaxin; Zhu, Peican (Frontiers in Physics, 2022)
Air transport is a long-distance journey, the main way of transnational travel, which is also an important connect channel between countries/regions. The Aviation network is one of the core national transportation networks, whose importance is self-evident. For better analysis of the aviation network to improve the management efficiency of the aviation network, this paper deeply studies the topological characteristics of the global aviation network. The findings show that the global aviation network is a scale-free heterogeneous network. And the aviation network is more tolerant to random faults. However, if key nodes are deliberately attacked, the network structure can easily be destroyed into fragments. To further explore the importance of nodes, combined with the background of airport merger or union, the node shrinkage method is improved by weighting network edges with the number of edges and ranking the importance of each node in the aviation network. This study compares the results of node importance calculation by the node shrinkage method and improved weighted node shrinkage method respectively. The results show that the ranking results obtained from the weighted node shrinkage method are better than that from the traditional node shrinkage method. To further verify the validity of the weighted node shrinkage method, this paper conducts sensitivity analysis by calculating the weights of nodes and edges with different values. The results imply that the rank changes of node importance in the top 20 global aviation networks are the same. Therefore, it is important to find the key nodes in the aviation network and take corresponding protective measures to protect the stability of the global aviation network and improve the efficiency of the management of the aviation network.